Anti-cracking auxiliary agent, anti-cracking auxiliary agent solution, electrode slurry, electrode pole piece and battery

By using an anti-cracking additive composed of unsaturated polyether phosphate and crosslinking agent in the electrode slurry, the problem of surface cracking during thick coating of the electrode sheet is solved, and the high-quality preparation of the electrode sheet and the improvement of battery performance is achieved.

CN119890308APending Publication Date: 2025-04-25RUIGU NEW ENERGY (SHANGHAI) MATERIAL TECH CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202311853476.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-12-28
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Currently, the surface is prone to cracking when the electrode sheet is coated, resulting in defects in the electrode sheet, deteriorating battery performance, and lack of effective additives to inhibit the occurrence of electrode sheet cracks.

Method used

An anti-cracking additive is provided, which contains unsaturated polyether phosphate and a crosslinking agent, which is used in the electrode slurry to suppress the generation of electrode sheet cracks and improve the quality of the electrode sheet.

Benefits of technology

By using anti-cracking additives, stress cracking during drying is reduced, and the electrode slurry is coated with thick coating without cracking, improving the quality of the electrode sheet and battery performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890308A_ABST
    Figure CN119890308A_ABST
Patent Text Reader

Abstract

The invention relates to an anti-cracking auxiliary agent, an anti-cracking auxiliary agent solution, electrode slurry, an electrode plate and a battery. The anti-cracking aid comprises unsaturated polyether phosphate and a cross-linking agent in a mass ratio of (1-19): 1; the cross-linking agent is an organic compound containing two or more carbon-carbon double bonds. The anti-cracking auxiliary agent solution comprises the anti-cracking auxiliary agent and a solvent. The electrode slurry comprises the anti-cracking auxiliary agent. The electrode plate is prepared from the electrode slurry. The battery comprises the electrode plate. The anti-cracking auxiliary agent can be used in the electrode slurry to inhibit the generation of cracks on the electrode plate and improve the quality of the electrode plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an anti-cracking agent, an anti-cracking agent solution, an electrode slurry, an electrode sheet, and a battery. Background Technology

[0002] With the development of lithium battery technology, thick electrode coating technology has become one of the most popular technological development directions. Developing thick electrode coating can significantly increase the loading of active materials and reduce the ratio of inactive components, thereby improving battery energy density while reducing costs.

[0003] However, current thick coating techniques for electrodes still face significant technical challenges. Thick coatings are prone to surface cracking, leading to surface defects that ultimately degrade battery performance. Currently, there is a lack of additives available for thick electrode coatings to suppress electrode crack formation. Summary of the Invention

[0004] To overcome the defect of easy surface cracking during thick coating of electrode sheets in existing technologies, this invention provides an anti-cracking agent, an anti-cracking agent solution, an electrode slurry, an electrode sheet, and a battery. The anti-cracking agent described in this invention can be used in the electrode slurry to inhibit the formation of cracks in the electrode sheet and improve the quality of the electrode sheet.

[0005] To solve the above problems and achieve the purpose of this invention, the following technical solution is adopted:

[0006] In a first aspect, the present invention provides an anti-cracking agent comprising an unsaturated polyether phosphate ester and a crosslinking agent in a mass ratio of (1-19):1;

[0007] The structural formula of the unsaturated polyether phosphate is shown in formula (I):

[0008]

[0009]

[0010] in,

[0011] X1 and X2 are each independently hydrogen or have the structure shown in formula (II), and X1 and X2 are not hydrogen at the same time;

[0012]

[0013] R1 is hydrogen or methyl, and R2 is a C1-C4 alkylene group, -CH2CH2O-, -CH2CH2OOC-, -CH2CH2CH2OOC-, -CH(CH3)CH2OOC-, or -CH2CH2CH2CH2OOC-;

[0014] n is 0-54, m is 0-25, and 5≤n+m≤54;

[0015] The crosslinking agent is an organic compound containing two or more carbon-carbon double bonds.

[0016] In this invention, R2 is preferably methylene, C2 alkylene, C4 alkylene, -CH2CH2O-, -CH2CH2OOC-, or -CH2CH2CH2CH2OOC-.

[0017] In this invention, n is preferably 7-45, for example 7, 9, 10, 13 or 45.

[0018] In this invention, m is preferably 5-10, for example 5 or 6.

[0019] In this invention, the unsaturated polyether phosphate may be one or more of the following: methyl allyl alcohol polyoxyethylene ether phosphate, allyl alcohol polyoxyethylene ether phosphate, isopentenyl alcohol polyoxyethylene ether phosphate, vinyl glycol polyoxyethylene ether phosphate, vinyl-4-hydroxybutyl polyoxyethylene ether phosphate, hydroxyethyl methacrylate polyoxyethylene ether phosphate, hydroxypropyl methacrylate polyoxyethylene ether phosphate, 4-hydroxybutyl acrylate polyoxyethylene polyoxypropylene ether phosphate, allyl alcohol polyoxypropylene ether phosphate, and 4-hydroxybutyl acrylate polyoxyethylene ether phosphate.

[0020] In some specific implementations, X1 is hydrogen, X2 is a structure as shown in formula (II), R1 is methyl, R2 is methylene, n is 10, and m is 0.

[0021] In some specific embodiments, X1 is hydrogen, X2 is a structure as shown in formula (II), R1 is methyl; R2 is a C2 alkylene; n is 13, and m is 0.

[0022] In some specific implementations, X1 is hydrogen, X2 is the structure shown in formula (II), R1 is hydrogen; R2 is -CH2CH2O-; n is 7, and m is 0.

[0023] In some specific embodiments, X1 is hydrogen, X2 is a structure as shown in formula (II), R1 is hydrogen, R2 is a C4 alkylene group, n is 45, and m is 0.

[0024] In some specific embodiments, X1 is hydrogen, X2 is a structure as shown in formula (II), R1 is methyl; R2 is -CH2CH2OOC-; n is 9, and m is 0.

[0025] In some specific implementations, X1 is hydrogen, X2 is the structure shown in formula (II), R1 is hydrogen; R2 is -CH2CH2CH2CH2OOC-; n is 10, and m is 5.

[0026] In some specific implementations, X1 is hydrogen, X2 is a structure as shown in formula (II), R1 is hydrogen, R2 is methylene, n is 0, and m is 6.

[0027] In this invention, the molecular weight of the unsaturated polyether phosphate is determined by the degree of polymerization and can be 300-1000.

[0028] In this invention, the crosslinking agent is preferably an acrylate compound or an allyl ether compound.

[0029] In some specific embodiments, the crosslinking agent is one or more selected from ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, polyethylene glycol diacrylate, dipropylene glycol diacrylate, ditripropylene glycol diacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, 2-(propoxy)neopentyl glycol diacrylate, bisphenol A diacrylate ethoxylate, diethylene glycol diacrylate phthalate, tricyclodecanediethanol dimethacrylate, trimethylolpropane triacrylate, ethoxytrimethylolpropane triacrylate, propoxytrimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, pentaerythritol triallyl ether, di-trimethylolpropane tetraacrylate, and dipentaerythritol hexaacrylate.

[0030] In this invention, the mass ratio of the unsaturated polyether phosphate ester to the crosslinking agent is preferably (3-6):1, for example 3:1, 4:1 or 5.67:1.

[0031] Secondly, the present invention provides an anti-cracking agent solution, which includes the anti-cracking agent and a solvent.

[0032] In this invention, the solvent may be one or more of methylpyrrolidone, toluene, xylene, propylene glycol methyl ether acetate, ethyl acetate, ethylene carbonate, acrylate carbonate, ethanol, and N,N-dimethylformamide.

[0033] In this invention, the concentration of the anti-cracking additive solution can be 10%-90%, for example 10%, 50%, 80% or 90%, where the percentage is the mass percentage of the anti-cracking additive in the anti-cracking additive solution.

[0034] Thirdly, the present invention provides an electrode paste comprising the anti-cracking agent as described above.

[0035] In this invention, the electrode slurry, based on 100% of the total solid mass, may include the following components by mass percentage: 93%-98% active material, 1%-4% conductive agent, 1%-3% binder, and 0.1%-0.5% anti-cracking agent.

[0036] The active material may comprise 96.75% of the total mass.

[0037] The conductive agent may account for 1% of the total mass.

[0038] The adhesive may comprise 2.0% of the total mass.

[0039] The anti-cracking agent may account for 0.25% of the total mass.

[0040] The active material may be one or more of carbon-coated lithium iron phosphate, lithium manganese iron phosphate, and nickel-cobalt-manganese ternary materials.

[0041] The conductive agent may be one or both of conductive carbon black and carbon nanotubes.

[0042] The adhesive may be PVDF.

[0043] In some specific embodiments, the electrode paste may include the following components in the following mass percentages: 96.75% carbon-coated lithium iron phosphate, 1% conductive graphite, 2% PVDF, and 0.25% anti-cracking agent.

[0044] Fourthly, the present invention provides an electrode sheet, which is made using the electrode paste described above.

[0045] In this invention, the method for preparing electrode sheets using the electrode slurry is conventional in the art and generally includes: coating the electrode slurry onto at least one surface of the current collector and drying it to obtain the electrode sheet.

[0046] In a preferred embodiment of the present invention, the electrode sheet is a positive electrode sheet.

[0047] Fifthly, the present invention provides a battery comprising the electrode plates as described above.

[0048] In this invention, the battery is preferably a lithium-ion battery.

[0049] Based on common knowledge in the field, the above-mentioned preferred conditions can be combined arbitrarily to obtain various preferred embodiments of the present invention.

[0050] The reagents and raw materials used in this invention are all commercially available.

[0051] The positive and progressive effects of this invention are as follows:

[0052] (1) In this invention, the anti-cracking agent also includes a crosslinking agent. During the drying process of the electrode sheet, the high temperature triggers the crosslinking of polyether phosphate and the crosslinking agent, thereby forming a network polymer film, which can further fix the components of the slurry, improve the stress bearing capacity of the components of the electrode slurry, reduce stress cracking during the drying process, and achieve thick coating of electrode slurry without cracking.

[0053] (2) The anti-cracking agent of the present invention contains unsaturated polyether phosphate as shown in formula (I), wherein the phosphate functional group can be used as an anchoring group, which can be adsorbed onto the surface of the active material to better disperse the electrode slurry and make the components of the electrode slurry more uniformly distributed.

[0054] Meanwhile, the polyether groups on the unsaturated polyether phosphate ester act as both solvation chains and flexible chains, providing steric hindrance. The polyether phosphate ester dispersant adsorbs onto the surface of the active material, which can reduce the aggregation of the active material particles and help disperse them. At the same time, the flexible polyether chains extend on the surface of the active material particles, forming a flexible solvation chain layer, which helps reduce the brittleness of the active material particles and improve their flexibility. Attached Figure Description

[0055] Figure 1 This is a photograph of the appearance of the positive electrode sheet after baking in the effect embodiment. Detailed Implementation

[0056] The present invention is further illustrated below by way of embodiments, but the invention is not limited to the scope of the embodiments described herein. Experimental methods in the following embodiments that do not specify specific conditions were performed according to conventional methods and conditions, or as selected according to the product instructions.

[0057] Examples 1-6 and Comparative Example 1

[0058] The components of the crack-resistant additive and the solvent were mixed according to the proportions in Table 1 to obtain the crack-resistant additive solution. The components of the crack-resistant additive solution are shown in Table 1.

[0059] Table 1 Main raw materials of Examples 1-6 and Comparative Example 1

[0060]

[0061] Application examples

[0062] The anti-cracking additive solutions from the above examples and comparative examples were used in the positive electrode slurry formulation at a mass ratio of 0.25%. The components of the lithium battery positive electrode slurry and NMP were wet homogenized using a planetary degassing machine to obtain the positive electrode slurry of the application example. The blank group was the positive electrode slurry obtained without any additives, and the amount of active material was adjusted to 97%. The proportion data of each component of the positive electrode slurry are shown in Table 2, and the amount of all components of the positive electrode slurry is shown in Table 3.

[0063] Table 2. Dosage of each major component in the cathode slurry

[0064]

[0065] Table 3 Dosage of each component in the cathode slurry

[0066]

[0067] PVDF is added in the form of 6wt% PVDF NMP adhesive solution, that is, 52.267g of adhesive solution is added, which contains 3.14g of PVDF.

[0068] The anti-cracking additive is added in the form of an anti-cracking additive solution as described in the examples or comparative examples. For example, in slurry 1, 0.436g of an anti-cracking additive solution with a mass concentration of 90% containing 0.392g of anti-cracking additive is added.

[0069] The solid content of the slurry refers to the percentage of solids by mass in the slurry. Table 3 shows the solids in the cathode slurry, including the folded solid mass of carbon-coated lithium iron phosphate, conductive agent, PVDF, and the folded solid mass of the anti-cracking additive in the anti-cracking agent solution.

[0070] Effect Example

[0071] The performance of each slurry (blank slurry, control slurry, and slurries 1-6) in the application examples was tested, including:

[0072] (1) Viscosity test

[0073] Viscosity testing was conducted using a digital rotational viscometer. After heating the sample to a constant temperature of 25°C, a No. 64 rotor was used. The digital data displayed after 3 minutes of testing was taken as the viscosity test data, and the results are shown in Table 4.

[0074] (2) Electrode cracking test

[0075] The obtained positive electrode slurry was coated onto the positive electrode carbon foil using a small automatic coating machine manufactured by Shenghua Industrial. The coating was applied to one side of the electrode, with a coating surface density of 25.5 mg / cm³. 2 Then, the coated foil was placed in a 120℃ forced-air drying oven and baked for 30 minutes. The surface cracking of the electrode was then observed, and the results are shown in Table 4. Figure 1 As shown:

[0076] Table 4. Test Results of Positive Electrode Slurry Performance

[0077] Discharge viscosity (mPa·s) Electrode cracking Blank slurry 9760 cracking Comparison of slurries 9320 Slight cracks Slurry 1 8960 No cracking Slurry 2 10320 No cracking Slurry 3 12240 No cracking Slurry 4 10560 No cracking Slurry 5 10240 No cracking Slurry 6 10680 No cracking

[0078] As shown in Table 4, compared to the blank slurry, the solid content of slurries 1-6 increased from 52% to 56%, but the viscosity remained close to that of the blank slurry. This indicates that the anti-cracking agent of the present invention can maintain a comparable viscosity even with a higher solid content. In other words, the anti-cracking agent of the present invention has a certain dispersion effect of reducing viscosity and increasing slurry solid content. Further comparison of the slurries shows that while using unsaturated phosphate dispersant alone has a certain dispersion and solid content-increasing effect, and reduces cracking compared to the blank slurry, its anti-cracking performance is not as good as that of slurries 1-6 with added crosslinking agent. This indicates that the anti-cracking agent of the present invention does indeed further improve the anti-cracking performance.

[0079] The above embodiments are merely preferred embodiments of the present invention and are only used to explain the present invention, not to limit the present invention. Any changes, substitutions, modifications, etc., made by those skilled in the art without departing from the spirit and essence of the present invention should be within the protection scope of the present invention.

Claims

1. An anti-cracking aid, characterized in that: It comprises an unsaturated polyether phosphate and a cross-linking agent in a mass ratio of (1-19):1; The structural formula of the unsaturated polyether phosphate is shown in formula (I): in, X1 and X2 are each independently hydrogen or a structure as shown in formula (II), and X1 and X2 are not hydrogen at the same time; R1 is hydrogen or methyl, R2 is C1-C4 alkylene, -CH2CH2O-, -CH2CH2OOC-, -CH2CH2CH2OOC-, -CH(CH3)CH2OOC- or -CH2CH2CH2CH2OOC-; n is 0-54, m is 0-25, and 5≤n+m≤54; The cross-linking agent is an organic compound containing two or more carbon-carbon double bonds.

2. The anti-cracking aid according to claim 1, characterized in that R2 is methylene, C2 alkylene, C4 alkylene, -CH2CH2O-, -CH2CH2OOC- or -CH2CH2CH2CH2OOC-; and / or, n is 7-45, such as 7, 9, 10, 13 or 45; and / or, m is 5-10, such as 5 or 6; And / or, the molecular weight of the unsaturated polyether phosphate is 300-1000; And / or, the cross-linking agent is an acrylate compound or an allyl ether compound, for example, one or more of ethylene glycol diacrylate, diethylene glycol diacrylate, triethylene glycol diacrylate, polyethylene glycol diacrylate, dipropylene glycol diacrylate, tripropylene glycol diacrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, neopentyl glycol diacrylate, 2 (propoxylated) neopentyl glycol diacrylate, ethoxylated bisphenol A diacrylate, diethylene glycol phthalate diacrylate, tricyclodecane dimethanol dimethacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, pentaerythritol triallyl ether, di-trimethylolpropane tetraacrylate and dipentaerythritol hexaacrylate; And / or, the mass ratio of the unsaturated polyether phosphate to the cross-linking agent is (3-6):1, such as 3:1, 4:1 or 5.67:

1.

3. The anti-cracking aid according to claim 1, characterized in that: The unsaturated polyether phosphate is one or more of methyl allyl alcohol polyoxyethylene ether phosphate, allyl alcohol polyoxyethylene ether phosphate, isopentanol polyoxyethylene ether phosphate, vinyl glycol polyoxyethylene ether phosphate, vinyl-4-hydroxybutyl polyoxyethylene ether phosphate, methacrylate hydroxyethyl polyoxyethylene ether phosphate, methacrylate hydroxypropyl polyoxyethylene ether phosphate, acrylate-4-hydroxybutyl polyoxyethylene polyoxypropylene ether phosphate, allyl alcohol polyoxypropylene ether phosphate and acrylate-4-hydroxybutyl polyoxyethylene ether phosphate; Preferably, the unsaturated polyether phosphate satisfies any one of the following conditions ①-⑦: ①X1 is hydrogen, X2 is a structure as shown in formula (II), R1 is a methyl group; R2 is a methylene group; n is 10, and m is 0; ②X1 is hydrogen, X2 is a structure as shown in formula (II), R1 is a methyl group; R2 is a C2 alkylene group; n is 13, and m is 0; ③X1 is hydrogen, X2 is a structure as shown in formula (II), R1 is hydrogen; R2 is -CH2CH2O-; n is 7, and m is 0; ④X1 is hydrogen, X2 is a structure as shown in formula (II), R1 is hydrogen; R2 is a C4 alkylene; n is 45, and m is 0; ⑤X1 is hydrogen, X2 is a structure as shown in formula (II), R1 is methyl; R2 is -CH2CH2OOC-; n is 9, and m is 0; ⑥X1 is hydrogen, X2 is a structure as shown in formula (II), R1 is hydrogen; R2 is -CH2CH2CH2CH2OOC-; n is 10, and m is 5; ⑦X1 is hydrogen, X2 is a structure as shown in formula (II), R1 is hydrogen; R2 is methylene; n is 0, and m is 6.

4. An anti-cracking additive solution, characterized in that: The invention comprises the anti-cracking aid as claimed in any one of claims 1 to 3 and a solvent.

5. The anti-cracking aid solution according to claim 4, characterized in that: The solvent is one or more of methyl pyrrolidone, toluene, xylene, propylene glycol methyl ether acetate, ethyl acetate, ethylene carbonate, acrylate carbonate, ethanol and N,N-dimethylformamide; And / or, the concentration of the anti-cracking aid solution is 10%-90%, such as 10%, 50%, 80% or 90%, where the percentage is the mass percentage of the anti-cracking aid in the anti-cracking aid solution.

6. An electrode slurry, characterized in that: It comprises the anti-cracking aid according to any one of claims 1 to 3.

7. The electrode slurry according to claim 6, characterized in that Based on 100% of the total solid mass, the electrode slurry includes the following components in proportion by mass: 93%-98% of active material, 1%-4% of conductive agent, 1%-3% of binder and 0.1%-0.5% of the anti-cracking aid.

8. The electrode slurry according to claim 7, characterized in that The active material is one or more of carbon-coated lithium iron phosphate, lithium iron manganese phosphate and nickel-cobalt-manganese ternary material; And / or, the conductive agent is one or both of conductive carbon black and carbon nanotubes; And / or, the binder is PVDF.

9. An electrode plate, characterized in that: The electrode slurry is prepared by using the electrode slurry as described in any one of claims 6 to 8.

10. A battery, characterized in that: It includes the electrode plate as claimed in claim 9.

Citation Information

Cited By

  • Anti-cracking auxiliary agent for lithium ion battery negative electrode and preparation method and application of anti-cracking auxiliary agent

    CN121554749A

  • Anti-cracking additive for lithium ion battery negative electrode and preparation method and application thereof

    CN121554749B

  • Preparation method of low-tortuosity positive pole piece and low-tortuosity positive pole piece

    CN121687871A

  • A composite additive for lithium ion batteries and application thereof

    CN122511903A